2020
DOI: 10.1083/jcb.202001063
|View full text |Cite
|
Sign up to set email alerts
|

The DNA damage response links human squamous proliferation with differentiation

Abstract: How rapid cell multiplication leads to cell differentiation in developing tissues is still enigmatic. This question is central to morphogenesis, cell number control, and homeostasis. Self-renewal epidermoid epithelia are continuously exposed to mutagens and are the most common target of cancer. Unknown mechanisms commit rapidly proliferating cells to post-mitotic terminal differentiation. We have over-activated or inhibited the endogenous DNA damage response (DDR) pathways by combinations of activating TopBP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…DNA damage has been linked to cell fate changes in several systems (Grow et al, 2021; Inomata et al, 2009; Kato et al, 2021; Molinuevo et al, 2020; Santos et al, 2014; Wang et al, 2012). To directly test whether DNA damage can cause differentiation in these cells, we used various DNA damaging agents.…”
Section: Resultsmentioning
confidence: 99%
“…DNA damage has been linked to cell fate changes in several systems (Grow et al, 2021; Inomata et al, 2009; Kato et al, 2021; Molinuevo et al, 2020; Santos et al, 2014; Wang et al, 2012). To directly test whether DNA damage can cause differentiation in these cells, we used various DNA damaging agents.…”
Section: Resultsmentioning
confidence: 99%
“…This would also fit with the induction of stress keratins (Supplementary File 3). In fact, it might be directly connected to the squamous differentiation phenotype, as keratinocytes are known to undergo differentiation in response to DNA damage and replication stress (Freije et al, 2014; Molinuevo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial tissue homeostasis is constantly challenged by exposure to pro-mutational injuries and, thus, robust protective mechanisms against malignant transformation are crucial. In this context, compelling evidence have shown that after genotoxic or oncogenic stress, epithelial cells activate a terminal differentiation program that has been proposed as a safeguard mechanism against oncogenic alterations [36][37][38] . Altogether, cell polarity and differentiation have been positioned as key tumor suppressive mechanisms and their disruption is considered a hallmark in epithelial cancers 33,39 .…”
mentioning
confidence: 99%